The Relationship between Cyber Security Knowledge, Awareness and Behavioural Choice Protection among Mobile Banking Users in Thailand - Limna, Pongsakorn; Kraiwanit, Tanpat; Siripipattanakul, Sutithep (International Journal of Computing Sciences Research, 2023)
Purpose – Mobile banking is becoming increasingly popular in Thailand. This study investigates the relationship between cyber security knowledge, awareness, and behavioural choice protection among mobile banking users in Thailand. Method – A quantitative approach was employed. The questionnaire was developed based on reliable and valid sources. The online questionnaire was adopted to collect the data through convenience sampling of 414 mobile banking users in Thailand. The data were analysed using SPSS Version 27 and ADANCO 2.3 for hypothesis testing. Results – The results reveal that cyber security knowledge significantly impacts cyber security awareness and behavioural choice protection. Cybersecurity awareness significantly impacts behavioural choice protection. Cyber security awareness significantly mediators between cyber security knowledge and behavioural choice protection. Conclusion – Cyber security knowledge and awareness are critical for influencing behavioural choice protection among Thai mobile banking users. As a result, banks must develop an effective cybersecurity strategy to meet the needs and expectations of mobile banking users. As a result, there may be an increase in mobile banking users, and high business performance may incur. Recommendations – This study employed sampling to explain only mobile banking from customers' perceptions. It may not cover other sectors. Hence, there should be increased sampling in a variety of industries. Furthermore, this study consists of a self-administered questionnaire for quantitative analysis. Thus, more insightful analysis through qualitative research could also explain the association between cyber security awareness, cyber security knowledge, and behavioural choice protection among mobile banking application customers or other sectors in Thailand. Research Implications – This study contributed to the existing literature on cyber security awareness, cyber security knowledge, and behavioural choice protection. Therefore, the findings of this study may help academics expand their research by incorporating additional potential factors. These metrics could guide future cybersecurity research and its outcomes in the digital era. Practical Implications – The implications could be applied to any sector in explaining the association between cybersecurity awareness, knowledge and behavioural choice protection among mobile banking application customers or other sectors in Thailand.